Zika Inquiries Made to the CDC-INFO System, December 2015–September 2017 - Sell, Tara Kirk (Emerg Infect Dis, 2020)
We examined Zika-related inquiries to CDC-INFO, the national contact center for the Centers for Disease Control and Prevention, to identify potential communication gaps. The most frequently asked questions related to travel or geographic location of Zika (42% of all inquiries), information about laboratory testing (13%), or acquiring a Zika test (11%).